The Role of Road Users’ Discipline in Mediating The Equipment Function and Gatekeeper Competence on Level Crossing Safety in 2025 (Case Study: Jpl No. 46 Pondok Jati, East Jakarta) - Dewi Suci Indrawati; Edhie Budi Setiawan; Abdulllah Ade Suryobuwono; Zaenal Abidin; Soemino Eko Saputro (Dinasti Publisher, 2025)
Level crossing safety has become a critical issue in urban transportation systems, as these points serve as direct intersections between railway lines and road users. Amidst the high volume of daily mobility, level crossings not only contribute to traffic congestion but also pose a high risk of fatal accidents, especially when not supported by effective safety systems and disciplined user behavior. A clear example of this issue can be seen at the Direct Level Crossing (JPL) No. 46 Pondok Jati in East Jakarta, which is characterized by high traffic density, limited space, and frequent violations by road users. This study aims to analyze the mediating role of road user discipline in the relationship between the functionality of safety equipment and the competence of crossing guards on level crossing safety in 2025. A quantitative approach was used with Structural Equation Modeling based on Partial Least Squares (SEM-PLS) and 333 respondents. The analysis tested both direct and indirect relationships among the variables. The results show that the competence of crossing guards significantly influences both safety and user discipline. Discipline also plays a significant role in improving safety. Conversely, the functionality of safety equipment did not show a significant direct influence on discipline. Discipline was found to mediate the relationship between guard competence and safety, but not between equipment functionality and safety.